PENDIDIKAN AGAMA ISLAM DI ERA INFORMASI SEBAGAI PEMBENTUKAN AKHLAK PESERTA DIDIK - Hibrul Umam (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2018)
Islamic religious education is an urgent matter to be studied for every human being, especially Muslims, because these subjects are very important for students especially in public schools. If not surprised, many students commit crimes everywhere, such as robbing, doing sex outside of marriage, disobeying both parents, not performing prayer and so on. So do not be surprised if Islamic religious education subjects are expected to be able to provide a thirst for their thirst (students) for the meaning of life and the importance of the future. Because Islamic religious education has a principle as a process of self-development, free education, education that is full of human and divine values, principles of life balance, principles of equality, principles of a lifetime, and self-principles. Islamic religious education subjects at least provide or shape the character of students especially in public schools with various approaches both cognitive, affective, and behavioral.